Childhood exposure to traffic-related air pollution and lung function at age 10 years: evidence of nutritional modification in a birth cohort - Yujin Park; Dong-Wook Lee; Choong Ho Shin; Young Ah Lee; Yun Jeong Lee; Dong In Suh; Yun-Chul Hong; Youn-Hee Lim; Bung-Nyun Kim; Johanna Inhyang Kim; Soontae Kim; Kyoung-Nam Kim (International Journal of Hygiene and Environmental Health, 2026)

Ubiquilin 1 Inhibits intracellular proliferation of Salmonella enterica serovar Typhimurium through Xenophagy - In Sook Jeon; Yong-Hee Lee; Jin Tae Hong; Won Seop Kim; Jae-Cheon Shin; Hak-Kyo Lee; Joong-Kook Choi (Genes & Genomics, 2026)

Dyella stictolepturae sp. nov., isolated from the larva gut of red-brown longhorn beetle (Stictoleptura succedanea) - Bora Kim; Ah-In Yang; Sung-Hong Joe; Hae-In Joe; Na-Ri Shin (Antonie van Leeuwenhoek, 2026)

Effects of web-based behavioral intervention on fine particulate matter, pulmonary function, and airway inflammation in children: The COCOA randomized controlled trial - Dirga Kumar Lamichhane; Bo-Mee Kim; Jungyun Bae; Hea Young Oh; Dong In Suh; Youn Ho Shin; Kyung Won Kim; Kangmo Ahn; Hyo-Bin Kim; Song-I Yang; So-Yeon Lee; Soo-Jong Hong; et al. (Environmental Research, 2025)

PM exposure during pregnancy affects childhood asthma via placental epigenetic changes: Neuronal differentiation and proliferation and Notch signaling pathways - Hyo-Bin Kim; Si Hyeon Lee; Dae Yeol Yang; Seung-Hwa Lee; Jeong-Hyun Kim; Hwan-Cheol Kim; Kil Yong Choi; So-Yeon Lee; Song-I Yang; Dong In Suh; Youn Ho Shin; Kyung Won Kim; et al. (Environmental Pollution, 2025)

Olaparib synergically exacerbates the radiation-induced intestinal apoptosis in mice - Sohee Jeong; Jeongmin Lee; Jun Hong Park; Yeonghoon Son; Hae-June Lee; Changjong Moon; In Sik Shin; Joong Sun Kim; Sohi Kang (Molecular & Cellular Toxicology, 2024)

Mechanochemical activation of silicon photothermal material for efficient interfacial solar desalination and wastewater purification - Tatachari Santhanagopalan Shridharan; Arumugam Sivanantham; Jong Ho Lee; Seo Yeong Hong; Yoo Jae Jeong; Seong Sik Shin; In Sun Cho (Chemical Engineering Journal, 2024)

Low-dose-rate gamma radiation aggravates titanium dioxide nanoparticle-induced lung injury in mice - Sohi Kang; Hae-June Lee; Yeonghoon Son; Min Ji Bae; Wol Soon Jo; Jun Hong Park; Sohee Jeong; Changjong Moon; In-Sik Shin; Chang Geun Lee; Joong Sun Kim (Molecular & Cellular Toxicology, 2024)

Submarine landslides on the Eastern South Korea Plateau (ESKP)—Do pumice-rich tephra layers control slope stability? - Deniz Cukur; In-Kwon Um; David M. Buchs; Seong-Pil Kim; Gee-Soo Kong; Jong-Hwa Chun; Senay Horozal; Seok-Hwi Hong; Shin Yu; Tae-Yeon Kim (Marine Geology, 2024)

Construction of an underwater plasma and Fenton hybrid system for the rapid oxidation of organic dyes and antibiotics - Soo Hyeon Kim; Jiwon Seo; Yongcheol Hong; Yongwook Shin; Hea-Jong Chung; Ha-Rim An; ChangYeon Kim; Ji-In Park; Hyun Uk Lee (Journal of Water Process Engineering, 2023)

Oculomics for sarcopenia prediction: a machine learning approach toward predictive, preventive, and personalized medicine - Bo Ram Kim; Tae Keun Yoo; Hong Kyu Kim; Ik Hee Ryu; Jin Kuk Kim; In Sik Lee; Jung Soo Kim; Dong-Hyeok Shin; Young-Sang Kim; Bom Taeck Kim (EPMA Journal, 2022)

First report of powdery mildew caused by Podosphaera xanthii on Matricaria chamomilla in Korea - In-Young Choi; Sun-Hee Hong; Yong-Ho Lee; Hyeon-Dong Shin (Journal of Plant Pathology, 2022)

The Neuropeptide Spexin Promotes the Osteoblast Differentiation of MC3T3-E1 Cells via the MEK/ERK Pathway and Bone Regeneration in a Mouse Calvarial Defect Model - Freshet Assefa; Ju Ang Kim; Jiwon Lim; Sang-Hyeon Nam; Hong-In Shin; Eui Kyun Park (Tissue Engineering and Regenerative Medicine, 2022)

First report of powdery mildew caused by Erysiphe polygoni on Rumex japonicus in Korea - In-Young Choi; Hyun-Myung Oh; Sun-Hee Hong; Young-Ho Lee; Hyeon-Dong Shin (Journal of Plant Pathology, 2022)

The optimal standard protocols for whole-genome sequencing of antibiotic-resistant pathogenic bacteria using third-generation sequencing platforms - Tae-Min La; Ji-hoon Kim; Taesoo Kim; Hong-Jae Lee; Yoonsuk Lee; Hyunjin Shin; Yongjun Song; Gyuhee Ahn; Won Hur; Joong-Bok Lee; Seung-Yong Park; In-Soo Choi; et al. (Molecular & Cellular Toxicology, 2021)

Effect of different planting times on the quantitative variation of total seed isoflavone content and composition in Korean soybean cultivars (Glycine max (L.) Merr.) - Hong-Sik Kim; Beom-Kyu Kang; Jeong-Hyun Seo; Hyun-Tae Kim; Tae-Joung Ha; Jae-Hyeon Oh; Sang-Ouk Shin; In-Yeol Baek (Journal of Crop Science and Biotechnology, 2021)
There is great interest in the enhancement of isoflavones as one of the functional ingredients in soybean. This study aimed to investigate the effects of changes in the ecological environment over different planting times on isoflavone content. A total of 28 Korean soybean cultivars were grown at different planting times in late May, mid-June, and early July and their isoflavone content was measured over 2 years (2017 and 2018). Analyses of variance revealed significant effects of genotypes, planting times, years, and their interactions on isoflavone content. The average content of total isoflavone, as well as its component groups of malonylglucoside and aglycon, increased significantly as the seed planting time was delayed from late May to early July. The accumulation of each isoflavone component varied with changes in the planting time. The isoflavone content of the soybean cultivars for soy-sprout and soy-paste and tofu were higher for plantings in early July than for those in late May and/or mid-June, except for the black soybean cultivars. Despite significant correlations of the isoflavone content of the 28 cultivars among the three planting times, the responses of individual cultivars varied in isoflavone content by planting time. When planting was delayed, the time to flowering and maturity was also delayed and the number of days of growth from planting or flowering to maturity decreased; however, this was not related to isoflavone content. When planting was delayed, the temperature during the ripening period from flowering to maturity was lower, which was inversely related to the isoflavone content.

Role of p53 in transcriptional repression of SVCT2 - Eun Ho Kim; Dong-In Koh; Yea Seong Ryu; Sang-Soo Park; Seung-Woo Hong; Jai-Hee Moon; Jae-Sik Shin; Mi Jin Kim; Do Yeon Kim; Jun Ki Hong; Hong-Rae Jeong; Hyeseon Yun; et al. (Molecular Biology Reports, 2021)

First report of powdery mildew caused by Podosphaera erigerontis-canadensis on Conyza sumatrensis in Korea - In-Young Choi; Sun-Hee Hong; Yong-Ho Lee; Hyeon-Dong Shin (Journal of Plant Pathology, 2021)

N-type Cav channel inhibition by spider venom peptide of Argiope bruennichi - In-Wook Hwang; Min Kyoung Shin; Yoo-Jung Lee; Seung Tae Kim; Sue Yeon Lee; Byungjo Lee; Wonhee Jang; Joo-Hong Yeo; Seungki Lee; Jung-Suk Sung (Molecular & Cellular Toxicology, 2021)

Analysis of differentially expressed genes in soybean leaf tissue of tolerant and susceptible cultivars under flooding stress revealed by RNA sequencing - Sanjeev K. Dhungana; Hong-Sik Kim; Beom-Kyu Kang; Jeong-Hyun Seo; Hyun-Tae Kim; Jae-Hyeon Oh; Sang-Ouk Shin; In-Yeol Baek (Journal of Crop Science and Biotechnology, 2021)
Flooding stress causes severe yield reduction in soybean worldwide. The development of stress-tolerant cultivars could be an effective measure to reduce the negative effects of flooding stress. Molecular information on the gene expression pattern of tolerant and susceptible genotypes under flooding stress could be valuable to improve the flooding tolerance in soybean. The objective of this study was to analyze the differentially expressed genes (DEGs) revealed by RNA sequencing in the soybean leaf tissues of tolerant (‘Paldalkong’ and ‘Danbaekkong’) and susceptible (‘NTS1116’) cultivars under flooding stress. Seedlings were grown in a well-watered condition up to the V1–V2 stage and flood-stressed by inundating ~ 10-cm water for 14 days. A total of 22,468 genes were differentially expressed in flood-stressed condition compared to the well-watered control condition, out of which 13,729, 13,405, and 13,160 were differentially expressed in ‘Paldalkong’, ‘Danbaekkong’, and ‘NTS1116’, respectively. A higher number of some of the flooding tolerance-related genes such as lipoxygenase, expansin, glutathione S-transferase, and sugar efflux transporter were up-regulated in the tolerant cultivars than in the susceptible cultivar. The number of some abscisic acid-related transcription factors of basic leucine zipper domain and myeloblastosis families was also higher in the tolerant cultivars than in the susceptible cultivar. The molecular information about the DEGs of tolerant and susceptible cultivars obtained in the present study could be valuable to improve the flooding tolerance in soybeans.

Targeting X chromosome-linked inhibitor of apoptosis protein in mucoepidermoid carcinoma of the head and neck: A novel therapeutic strategy using nitidine chloride - Hye-Jeong Kwon; Kyungsil Yoon; Ji-Youn Jung; Mi Heon Ryu; Sung-Hyun Kim; Eun-Seon Yoo; So-Young Choi; In-Hyoung Yang; Seong Doo Hong; Ji-Ae Shin; Sung-Dae Cho (Journal of Molecular Medicine, 2020)

High-density linkage map reveals QTL for Type-I seed coat cracking in RIL population of soybean [Glycine max (L.) Merr.] - Beom Kyu Kang; Jeong Hyun Seo; Hyun Jo; Krishnanand P. Kulkarni; Man Soo Choi; Hyun Tae Kim; Jeong Dong Lee; Sanjeev K. Dhungana; Hong Sik Kim; Jae Hyeon Oh; Ji Hee Park; Sang Ouk Shin; et al. (Euphytica, 2020)
Seed coat cracking (SCC), particularly the Type-I irregular cracking, is critical in determining the quality of appearance and commercial value of soybean seeds. The objective of this study was to identify the quantitative trait loci (QTLs) for SCC with high-density genetic map. One hundred sixty-seven recombinant inbred lines (RILs) developed from a cross between Uram (SCC-resistant) and Chamol (SCC-susceptible) were evaluated for SCC over 2 years (2016–2017). The QTL analysis identified 12 QTLs located on chromosomes 2 (D1b), 6 (C2), 8 (A2), 9 (K), 10 (O), 12 (H), 19 (L), and 20 (I). Out of the 12 QTLs, qSC2-1 , qSC9, SC10-1 , qSC10-2 , and qSC12 were novel QTLs and the other seven QTLs ( qSC2-2 , qSC2-3 , qSC6 , qSC8 , qSC19-1 , qSC19-2 , and qSC20 ) were found to co-localize with the previously identified QTLs. The mean SCC of the RILs of early maturity group was significantly higher than that of the late maturity group, suggesting an association between SCC and maturity loci. In addition, although 10 QTLs were distantly located from the maturity loci ( E1 , E3 , E4 , E7 , and E10 ), qSC10-1 and qSC10-2 co-localized with the maturity loci E2 . The results obtained in this study provide useful genetic information on SCC which could be used in the SCC breeding programs.

Neuronal loss and gliosis in the rat striatum subjected to 15 and 30 minutes of middle cerebral artery occlusion - Joon Ha Park; Jeong Hwi Cho; Ji Hyeon Ahn; Soo Young Choi; Tae-Kyeong Lee; Jae-Chul Lee; Bich Na Shin; Seongkweon Hong; Yong Hwan Jeon; Young-Myeong Kim; In Koo Hwang; Young Joo Lee; et al. (Metabolic Brain Disease, 2018)

Whitening and anti-wrinkle activities of ferulic acid isolated from Tetragonia tetragonioides in B16F10 melanoma and CCD-986sk fibroblast cells - Hye-Jin Park; Jun-Hyo Cho; Shin-Hyub Hong; Dong-Hee Kim; Hee-Young Jung; In-Kyu Kang; Young-Je Cho (Journal of Natural Medicines, 2018)

Effects of vascular formation during alveolar bone process morphogenesis in mice - Seo-Young An; Ye-Ji Lee; Sanjiv Neupane; Jong-Hwa Jun; Ji-Youn Kim; Youngkyun Lee; Karp-Shik Choi; Chang-Hyeon An; Jo-Young Suh; Hong-In Shin; Wern-Joo Sohn; Jae-Young Kim (Histochemistry and Cell Biology, 2017)

Extracellular calcium-binding peptide-modified ceramics stimulate regeneration of calvarial bone defects - Ju Ang Kim; Young-Ae Choi; Hui-Suk Yun; Yong Chul Bae; Hong-In Shin; Eui Kyun Park (Tissue Engineering and Regenerative Medicine, 2016)

Mesenchymal signaling in dorsoventral differentiation of palatal epithelium - Wern-Joo Sohn; Gi-Jeong Gwon; Hyeng-Soo Kim; Sanjiv Neupane; Sung-Jin Cho; Jae-Hyung Lee; Hitoshi Yamamoto; Je-Yong Choi; Chang-Hyeon An; Youngkyun Lee; Hong-In Shin; Sanggyu Lee; et al. (Cell and Tissue Research, 2015)

The role of APCDD1 in epithelial rearrangement in tooth morphogenesis - Sanjiv Neupane; Wern-Joo Sohn; Gi-Jeong Gwon; Ki-Rim Kim; Sanggyu Lee; Chang-Hyeon An; Jo-Young Suh; Hong-In Shin; Hitoshi Yamamoto; Sung-Won Cho; Youngkyun Lee; Jae-Young Kim (Histochemistry and Cell Biology, 2015)

Plant growth-promoting potential of endophytic fungi isolated from Solanum nigrum leaves - Abdur Rahim Khan; Ihsan Ullah; Muhammad Waqas; Raheem Shahzad; Sung-Jun Hong; Gun-Seok Park; Byung Kwon Jung; In-Jung Lee; Jae-Ho Shin (World Journal of Microbiology and Biotechnology, 2015)

Improvement in phytoremediation potential of Solanum nigrum under cadmium contamination through endophytic-assisted Serratia sp. RSC-14 inoculation - Abdur Rahim Khan; Ihsan Ullah; Abdul Latif Khan; Gun-Seok Park; Muhammad Waqas; Sung-Jun Hong; Byung Kwon Jung; Yunyoung Kwak; In-Jung Lee; Jae-Ho Shin (Environmental Science and Pollution Research, 2015)

Relationship between cold hardiness and dehydrin gene expression in peach shoot tissues under field conditions - Hyunsuk Shin; Sung-Il Oh; Min-Ah Kim; Seok Kyu Yun; Youngjae Oh; In-Chang Son; Hong-Sig Kim; Daeil Kim (Horticulture, Environment, and Biotechnology, 2015)

Phytostabilization and Physicochemical Responses of Korean Ecotype Solanum nigrum L. to Cadmium Contamination - Abdur Rahim Khan; Ihsan Ullah; Abdul Latif Khan; Sung-Jun Hong; Muhammad Waqas; Gun-Seok Park; Yunyoung Kwak; JungBae Choi; Byung-Kwon Jung; Man Park; In-Jung Lee; Jae-Ho Shin (Water, Air, & Soil Pollution, 2014)

Developmental regulations of Perp in mice molar morphogenesis - Sanjiv Neupane; Wern-Joo Sohn; Girdhari Rijal; Ye-Ji Lee; Sanggyu Lee; Hitoshi Yamamoto; Chang-Hyeon An; Sung-Won Cho; Youngkyun Lee; Hong-In Shin; Tae-Yub Kwon; Jae-Young Kim (Cell and Tissue Research, 2014)

Comparative transcriptomic analysis to identify differentially expressed genes in fat tissue of adult Berkshire and Jeju Native Pig using RNA-seq - Simrinder Singh Sodhi; Won Cheoul Park; Mrinmoy Ghosh; Jin Nam Kim; Neelesh Sharma; Kwang Yun Shin; In Cheol Cho; Youn Chul Ryu; Sung Jong Oh; Sung Hoon Kim; Ki-Duk Song; Sang Pyo Hong; et al. (Molecular Biology Reports, 2014)

SMOC1-induced osteoblast differentiation involves enhanced proliferation of human bone marrow mesenchymal stem cells - Young-Ae Choi; Dong-Sung Kim; Hong-In Shin; Eui Kyun Park (Tissue Engineering and Regenerative Medicine, 2014)

Antimicrobial peptides in the centipede Scolopendra subspinipes mutilans - Won Gi Yoo; Joon Ha Lee; Younhee Shin; Jae-Young Shim; Myunghee Jung; Byeong-Chul Kang; Jaedon Oh; Jiyeon Seong; Hak Kyo Lee; Hong Sik Kong; Ki-Duk Song; Eun-Young Yun; et al. (Functional & Integrative Genomics, 2014)

Osteogenic activity of chitosan-based hybrid scaffold prepared by polyelectrolyte complex formation with alginate - Seung Hwan Lee; Ho Yun Chung; Hong-In Shin; Dong-Joon Park; Jin Hyun Choi (Tissue Engineering and Regenerative Medicine, 2014)

Transcriptional activation of p21WAF1/CIP1 is mediated by increased DNA binding activity and increased interaction between p53 and Sp1 via phosphorylation during replicative senescence of human embryonic fibroblasts - Hyun-Seok Kim; Jee-In Heo; Seong-Hoon Park; Jong-Yeon Shin; Hong-Jun Kang; Min-Ju Kim; Sung Chan Kim; Jaebong Kim; Jae-Bong Park; Jae-Yong Lee (Molecular Biology Reports, 2014)

Comparison of bone regeneration rate in flat and long bone defects: Calvarial and tibial bone - Jiwon Lim; Jongman Lee; Hui-Suk Yun; Hong-In Shin; Eui Kyun Park (Tissue Engineering and Regenerative Medicine, 2013)

Characterization of functional variants in 33 blood pressure loci using 1000 genomes project data - Ji Eun Lim; Young-Ah Shin; Kyung-Won Hong; Hyun-Seok Jin; In Song Koh; Bermseok Oh (Genes & Genomics, 2013)

Prediction of the tacrolimus population pharmacokinetic parameters according to CYP3A5 genotype and clinical factors using NONMEM in adult kidney transplant recipients - Nayoung Han; Hwi-yeol Yun; Jin-yi Hong; In-Wha Kim; Eunhee Ji; Su Hyun Hong; Yon Su Kim; Jongwon Ha; Wan Gyoon Shin; Jung Mi Oh (European Journal of Clinical Pharmacology, 2013)

ATM mediates interdependent activation of p53 and ERK through formation of a ternary complex with p-p53 and p-ERK in response to DNA damage - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Minju Kim; Sung Chan Kim; Jae-Bong Park; et al. (Molecular Biology Reports, 2012)

Porcine SPP1 gene polymorphism association with phenotypic traits in the Landrace × Jeju (Korea) black pig F2 population - Sang-Hyun Han; Kwang-Yun Shin; Sung-Soo Lee; Moon-Suck Ko; Hong-Shik Oh; In-Cheol Cho (Molecular Biology Reports, 2012)

Reciprocal interactions of Fgf10/Fgfr2b modulate the mouse tongue epithelial differentiation - Wern-Joo Sohn; Hye-In Jung; Min-A Choi; Jin-Hyun Han; Gi-Jeong Gwon; Hitoshi Yamamoto; Sanggyu Lee; Zae Young Ryoo; Eui-Kyun Park; Hong-In Shin; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

A genome-wide association analysis reveals 1p31 and 2p13.3 as susceptibility loci for Kawasaki disease - Jae-Jung Kim; Young Mi Hong; Saejung Sohn; Gi Young Jang; Kee-Soo Ha; Sin Weon Yun; Myung Ki Han; Kyung-Yil Lee; Min Seob Song; Hyoung Doo Lee; Dong Soo Kim; Jong-Eun Lee; et al. (Human Genetics, 2011)

Importance of region-specific epithelial rearrangements in mouse rugae development - Wern-Joo Sohn; Hitoshi Yamamoto; Hong-In Shin; Zae Young Ryoo; Sanggyu Lee; Yong-Chul Bae; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

ERK mediates anti-apoptotic effect through phosphorylation and cytoplasmic localization of p21Waf1/Cip1/Sdi in response to DNA damage in normal human embryonic fibroblast (HEF) cells - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Sung Chan Kim; Jae-Bong Park; Jaebong Kim; et al. (Molecular Biology Reports, 2011)

A possible association of EMID2 polymorphisms with aspirin hypersensitivity in asthma - Charisse Flerida A. Pasaje; Jeong-Hyun Kim; Byung-Lae Park; Hyun Sub Cheong; Mi-Kyeong Kim; Inseon S. Choi; Sang Heon Cho; Chein-Soo Hong; Yong Won Lee; Jae-Young Lee; In Song Koh; Tae-Joon Park; et al. (Immunogenetics, 2011)

SINE indel polymorphism of AGL gene and association with growth and carcass traits in Landrace × Jeju black pig F2 population - Sang-Hyun Han; Kwang-Yun Shin; Sung-Soo Lee; Moon-Suck Ko; Dong Kee Jeong; Hong-Shik Oh; Byoung-Chul Yang; In-Cheol Cho (Molecular Biology Reports, 2010)

Sulindac induces apoptotic cell death in susceptible human breast cancer cells through, at least in part, inhibition of IKKβ - A-Mi Seo; Seung-Woo Hong; Jae-Sik Shin; In-Chul Park; Nam-Joo Hong; Dae-Jin Kim; Won-Keun Lee; Wang-Jae Lee; Dong-Hoon Jin; Myeong-Sok Lee (Apoptosis, 2009)

Gibberellin production and phosphate solubilization by newly isolated strain of Acinetobacter calcoaceticus and its effect on plant growth - Sang-Mo Kang; Gil-Jae Joo; Muhammad Hamayun; Chae-In Na; Dong-Hyun Shin; Hak Youn Kim; Jin-Kyu Hong; In-Jung Lee (Biotechnology Letters, 2009)

Perfluorooctanoic acid-induced hepatic toxicity following 21-day oral exposure in mice - Hee-Young Son; Sang-Hyun Kim; Hong-In Shin; Han Ik Bae; Jae-Ho Yang (Archives of Toxicology, 2008)

Angiotensin II type 1 receptor 1166A/C polymorphism in association with blood pressure response to exogenous angiotensin II - Hyeong-Seok Lim; Joo-Youn Cho; Dal-Seok Oh; Jae-Yong Chung; Kyoung-Sup Hong; Kyun-Seop Bae; Kyung-Sang Yu; Kyung-Hoon Lee; In-Jin Jang; Sang-Goo Shin (European Journal of Clinical Pharmacology, 2006)

Recombinant expression of human cathelicidin (hCAP18/LL-37) in Pichia pastoris - In-Pyo Hong; Sung-Jae Lee; Yong-Seok Kim; Shin-Geon Choi (Biotechnology Letters, 2006)

Isolation and characterization of a myo-inositol 1-phosphate synthase cDNA from developing sesame (Sesamum indicum L.) seeds: functional and differential expression, and salt-induced transcription during germination - Jae-An Chun; Un-Ho Jin; Jin-Woo Lee; Young-Byung Yi; Nam-In Hyung; Myung-Hwa Kang; Jae-Ho Pyee; Mi Suh; Churl-Whan Kang; Hong-Yeol Seo; Shin-Woo Lee; Chung-Han Chung (Planta, 2003)